An Assessment of the Values of French Colonial Townhouses in Hanoi Towards A More Sustainable Conservation - Tran, Quoc Bao; Nguyen, Quang Minh; Nguyen, Hai Van Hien; Vu, Thi Huong Lan; Dang, Viet Long (International Journal of Sustainable Construction Engineering and Technology, 2023)
As the capital city of French Indochina, Hanoi was well planned by the French and immensely invested in the construction of public buildings as well as houses. In addition to public buildings and villas designed in French colonial styles that shaped the so-called distinctive architectural heritage in Hanoi throughout the colonial years, a large number of townhouses built during 1920 - 1950 which formed the cityscape of Hanoi in the first half of the 20th century should be noted. After nearly 70 years since the French army withdrew from the city, the number of French townhouses has considerably decreased. The remaining houses have shown that this is a real “treasure” that needs to be conserved because of their important values, not only in terms of urban architecture but also in cultural and historical aspects. However, a fact requiring special attention is that French townhouses in Hanoi - unlike French public buildings and villas - have not yet been recognised as heritage so that they can be kept to avoid the risk of deterioration or demolition under the impact of rapid urbanisation in the market economy. One of the main reasons for this negative urban development is that there has been no concrete or comprehensive rating system to assess the values of those townhouses which will closely correspond to their characteristics and contexts. Therefore, the authors - based on site surveys and by applying some appropriate methods such as expert consultations and case studies - have developed a full set of criteria to help evaluate those remaining townhouses as accurately as possible. This system can be used as a basis for a systematic assessment and classification towards a more effective conservation and even promoting the values of those townhouses with regard to the development of a modern society and in consideration of sustainable heritage conservation as a mainstream in the world.